Love and Freedom in the Thought of Jalaluddin Rumi: A Contemporary Philosophical Study - Patriawati, Salma Junia; Nafsih, Syarifatun (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This article examines the concepts of love and freedom in the thought of Jalaluddin Rumi and analyzes their relevance to contemporary philosophical and humanitarian issues. The study employs qualitative library research by analyzing Rumi’s primary works, including Mathnawi, Fihi Ma Fihi, and Diwan-e Shams, supported by relevant secondary literature. A philosophical hermeneutic approach is used to interpret Rumi’s symbolic language and metaphors in order to uncover their underlying philosophical and spiritual meanings. The findings show that Rumi understands love (mahabbah) as an ontological principle that connects human beings with God, others, and the universe, and functions as the foundation of ethical life. Freedom (hurriyyah), in Rumi’s perspective, is not external or absolute autonomy, but inner freedom achieved through liberation from ego, desires, and worldly attachments. The integration of love and inner freedom forms a coherent spiritual framework that offers a critical perspective on modern understandings of freedom that tend to be individualistic and value-neutral. This study concludes that Rumi’s thought provides a relevant philosophical contribution to contemporary discussions on ethics, spirituality, and the search for meaning, while remaining grounded in the Islamic intellectual tradition.